Negotiating Faith and Culture: The Mauludhu Tradition in Bau-Bau amid Global Disruption - Hasni Hasan (UIN Sjech M. Djamil Djambek Bukittinggi, 2025)
This study explores the Mauludhu tradition in Bau-Bau as a means of integrating Islamic principles with local culture, showing resilience amid global disruptions. Mauludhu, celebrating the Prophet Muhammad's (peace be upon him) birth, is both a religious rite and a cultural event that bonds the community. In Bau-Bau, it emphasizes local uniqueness through traditional foods, cultural processions, and cross-generational participation. Amid challenges like climate change, digital shifts, and social fragmentation, Mauludhu adapts by preserving its spiritual core while responding to modern changes. The research uses a qualitative method, including literature review and documentation, to analyze symbolic meanings, implementation dynamics, and social functions. Results indicate that the tradition helps preserve Islamic values, strengthen social ties, and educate younger generations culturally. The incorporation of digital media and youth involvement shows how the tradition evolves to stay relevant. Overall, Bau-Bau’s Mauludhu demonstrates that religion and local culture are adaptable and dynamic forces capable of maintaining their identities amid globalization. It stands as a pillar of cultural resilience and religious devotion in a rapidly changing world.